Penerapan Model Problem Based Learning (PBL) Berbantuan Media Pop-Up Book untuk Meningkatkan Hasil Belajar pada Mata Pelajaran Tematik Kelas VI di SDN 44 Cakranegara - Atmi, Atmi Izzah Nursafitri; Hj. Nurhasanah; Efendi Harahap (Mataram University, 2025)
Twenty-first-century learning demands innovation in teaching methods and media to enhance learning outcomes effectively. One strategy that can be applied is Problem-Based Learning (PBL) assisted by Pop-Up Book media, which creates a more engaging and interactive learning atmosphere. This study aims to analyze the effectiveness of implementing the PBL model assisted by Pop-Up Book media in improving the learning outcomes of sixth-grade students at SDN 44 Cakranegara. The research employed Classroom Action Research (CAR) conducted in two cycles, involving 25 sixth-grade students as research subjects. The instruments used included learning outcome tests, observations, questionnaires, and documentation, which were analyzed descriptively and quantitatively by measuring mastery learning based on the Minimum Mastery Criteria (KKM). The results showed that before implementing PBL with Pop-Up Book media, the students’ average score was only 54, with a mastery rate of 24%. After the first cycle, the mastery rate increased to 60%, though some students still struggled to understand the material. In the second cycle, after improvements such as more intensive teacher guidance and clearer group task distribution, the mastery rate increased significantly to 84%. Therefore, the implementation of the PBL model assisted by Pop-Up Book media proved to be effective in improving students’ learning outcomes.